The Impact Of Digital Marketing Using Online Ordering Platforms On Increasing Income And Sustainability Of MSMEs Culinary Food Court Polonia Sky Park Medan - Miftah Faridh Nasir; Maya Syahlina (Jurnal Ekonomi, 2024)
The emergence of online food delivery platforms GoFood, GrabFood, and ShopeeFood helps MSMEs run their businesses. Polonia Sky Park Food Court Culinary UMKM is a combination of business actors in the culinary sector in the city of Medan. Polonia Sky Park Food Court Culinary MSMEs have collaborated with GoFood, GrabFood, and ShopeeFood. The research aims to find out how digital marketing strategies are implemented by the Polonia Sky Park Medan Culinary Food Court MSMEs to increase income and what impact the use of GoFood, GrabFood, and ShopeeFood has in increasing the Polonia Sky Park Medan Culinary Food Court MSMEs income after using the platform. The research uses descriptive qualitative methods. Types and sources of data use primary data collected directly from the main source and secondary data that previously existed and were used by researchers to complete the data. The data collection technique is in the form of interviews and documentation, which collect data about the research object and then analyze it to answer the problems at the Polonia Sky Park Medan Culinary Food Court MSMEs. Research shows that using an online food delivery platform can increase the income of Polonia Sky Park Medan Culinary Food Court MSMEs.